فاعلية برنامج الكورت لتدريس القراءة في تنمية التحصيل الدراسي ومهارات التفكير الناقد اطلاب الصف السابع بدولة قطر - Sayed Ibrahim Hussein Mohamed Sharfeldin (Universiti Sains Islam Malaysia, 2024)
Reading is very important for all school subjects. It is the bridge on which information is transferred to the minds of the students. High percentage of failure in the Arabic language was detected among grade seven Qatari students in addition to low percentage of academic achievement for the preparatory stage in Qatar in general. Furthermore, the development of students’ thinking skills became the focus of attention for many educators around the world. The problem of the study lies in searching for an educational program that assists student’s interaction and stimulates their thinking. This study aimed to recognize the effectiveness of the CoRT reading program in developing the academic achievement and critical thinking skills of grade seven students in Qatar. The study sample consisted of 63 students from Abu Obaida Preparatory School for Boys. The experimental group, which consisted of 33 students, was taught using the first CoRT Program (Breadth). The control group, which consisted of 30 students, was taught using the traditional method. The researcher applied the semi-experimental method in his study. The study tools consisted of: the first CoRT program (Breadth), an integration plan between the program and the reading curriculum, an academic achievement test of the reading skill and a critical thinking test. An independent sample t-test, paired sample t-test and Analysis of Covariance (Ancova) were used in the pre-tests and the post tests. The study used Cohen’s size of effect equation (Cohen’s D) to evaluate the impact of the program and its effectiveness in achieving the objectives of the study. The study results demonstrated significant statistical differences in the performance level of the experimental group students in both academic achievement and critical thinking skills in the post test. The study contributed to the improvement of the students’ academic achievement and critical thinking skills level through teaching reading skill for grade seven students. Further besides that, the study presented material that covered some of the shortage in the studies related to teaching thinking programs that help Arabic language teachers develop thinking skills inside the classroom. The study also provided a guide for Arabic teachers in integrating both critical thinking competencies and CoRT skills in reading teaching.